Functional Richness and Resilience in Coral Reef Communities - Carturan, Bruno S.; Parrott, Lael; Pither, Jason (Frontiers in Ecology and Evolution, 2022)
Within the Anthropocene the functional diversity of coral communities is changing rapidly, putting the resilience of many coral reef ecosystems in jeopardy. A better understanding of the relationship between coral functional diversity and reef resilience could reveal practical ways to achieve increased resilience. However, manipulating coral diversity experimentally is challenging, and consequently the links between coral functional diversity, resilience, and ecosystem functioning remain obscure. We used an ecologically detailed agent-based model to conduct a virtual experiment in which functional diversity was manipulated over the entire trait space of scleractinian corals. Using an imputed trait dataset of 798 coral species and eight key functional traits, we assembled 245 functionally distinct coral communities, which we subjected to a cyclone and bleaching event. We then measured four different aspects of their resilience and quantified for each measure the respective effect of (i) the functional richness (FRic), and (ii) community weighted means (CWM) of four types of trait: effect, resistance, recovery, and competitive. FRic represents the volume occupied by a community in the functional space, while CWM indicates the location of the communities’ centroid in the functional space. We found a significant and positive effect of FRic on three measures of resilience: communities with higher FRic recovered surface cover faster and had more rugosity and cover ten years after the disturbances. In contrast, the resistance of the coral community—i.e., the capacity to maintain surface cover when subjected to the disturbances—was independent of FRic and was determined primarily by the CWM of resistance traits. By analysing community dynamics and functional trade-offs, we show that FRic increases resilience via the selection and the insurance effects due to the presence of competitive species in the functional space, i.e., those highly dominant species that contribute the most to the complexity of the habitat and recover quickly from disturbances. Building from these results, we discuss the potential for FRic to serve as a proxy measure of resilience and we present a strategy that can provide direction to on-going reef restoration efforts, and pave the way for sustaining coral communities in a context of rapid global change.